Triple Open Dislocation in the Index Finger of the Hand Without a High-Energy Trauma - Utrillas, María Amparo Fontestad; Armiño, Paúl Vicente Alonso de; Rodrigo, Marta Sancho (Revista Chilena de Ortopedia y Traumatología, 2020)
A simultaneous double dislocation (both proximal [PIP] and distal [DIP] interphalangeal joints) of a triphalangeal finger is a rare entity. The most common hand affected is the right hand. In the case of a closed triple dislocation (metacarpophalangeal [MCP], PIP and DIP joints); there are only two cases in the literature revised. In this case, we report an open triple dislocation in the index finger of the left-hand of a 54-year-old man treated by closed reduction and 3 weeks of immobilization followed by active mobilization with satisfactory results.Level of evidence 3
Keywords: triple; abierta; luxación; mano